Women Issues from the Point of View of Simin Behbahani, an Iranian Poet - Ebrahimi, Maryam; Ebrahimi, Mokhtar (Journal of History Culture and Art Research, 2017)
Schematization of women’s issues and atypical psychic and psychological situation are significant issues that are manifested in Simin Behbahani’s poetries. In this contemporary poet’s thought, women’s issues have been expressed in a way that can reveal some kinds of feminist attitudes and trends. In other words, psychic and psychological situations of women, even their physical situation, are known as results of men’s atypical behaviors. In terms of plotting of women issues and the solution of their psychic and spiritual problem, she expresses the issue of men’s behavioral reformation. Although she does not recommend directly how men should behave, she portrays false behaviors of men in order to focus on the reverse of those behaviors. Therefore, Simin Behbahani’s feminism wants a temperate (moderate) style for social reformation of both men and women.